Uji Mutagenik β-Karoten Alga Merah Rhodymenia Pseudopalmata terhadap Mencit Jantan Galur Balb/C yang Diinduksi 7,12-Dimetilbenzen (A)Antrasen (DMBA) - Astutiningsih, Christina; Limantara, Leenawaty; Radjasa, Ocky K. (Biosaintifika: Journal of Biology & Biology Education, 2010)
Carotenoids are important biological compounds in cancer prevention because theycan inhibit the formation of free radicals, which react directly with oxygen. This researchwas aimed to determine the effect of antimutagenic â-carotene on 7.12-dimetilbenz(a)antracene (DMBA)-induced mice. From the observation of the mortality rate during theresearch period, the DMBA group showed the highest rate of mortality compared to thecontrol group and the groups of â-carotene isolates. The incidence of tumors showed thedeclining trend in the groups of test animals that were given with the increasing dosesof β-caroten isolate, i.e. 1.82; 3.64 and 7.28 mg kg-1 BW. The result may be caused bythe increasingly high levels of â-carotene in the test solutions, resulting in the lowertissue damage and the inhibited growth of tumors in the lungs. Based on Kruskal-Wallisstatistical analysis conducted on lung histology observational data for ten samples ofeach treatment group, it was confi rmed that there were signifi cant differences betweentreatments, which mean that â-carotene isolates can inhibit cancer growth in lung andskin of DMBA-induced animals.Keywords: β-carotene isolate, antimutagenic, DMBA (7,12-dimetilbenz(a)antracene)